Active Template Synthesis of Protein Heterocatenanes. (12th July 2019) - Da, Xiao‐Di; Zhang, Wen‐Bin
Abstract: Covalent‐bond‐forming protein domains can be versatile tools for creating unconventional protein topologies. In this study, through rewiring the SpyTag–SpyCatcher complex to induce rationally designed chain entanglement, we developed a biologically enabled active template for the concise, modular, and programmable synthesis of protein heterocatenanes both in vitro and in vivo. It is a general and good‐yielding reaction for forming heterocatenanes with precisely controlled ring sizes and broad structural diversity. More importantly, such heterocatenation not only provides an efficient means of bioconjugation for integrating multiple native functions, but also enhances the stability of the component proteins against proteolytic digestion, thermal unfolding, and freeze/thaw‐induced mechanical denaturation, thus opening up a versatile path in the nascent field of protein‐topology engineering. Abstract : Die Bildung von Protein‐Heterocatenanen wurde mithilfe eines aktiven Templats erreicht, das durch Modifizieren der Konnektivität des SpyTag‐SpyCatcher‐Komplexes erhalten wurde. Protein‐Heterocatenane sind resistenter gegen proteolytische Spaltung, thermische Entfaltung und Einfrieren/Auftauen als ihre einzelnen Bestandteile. Die genetisch kodierbare Methode liefert einen effizienten Weg zur Integration mehrerer Proteine in einen Komplex jenseits einfacher Fusion.